2022
DOI: 10.2298/tsci2203707l
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-physiological comfort properties of different woven fabrics used in sportswear for outdoor activities

Abstract: In this study, the thermo-physiological wear comfort is mainly characterized by the thermal and water vapor resistance performance of the woven fabrics used as sportswear for outdoor activities. The commonly used twill woven fabric with different thicknesses, weight, and density are selected for the experimental analysis, and it finds that fabric weight and thickness have crucial effects on the thermal resistance, and the water vapor resistance depends linearly on density and thickness. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Abbas et al [4] reported higher values of 0.078 W/m.K for cotton woven fabrics coated with graphene, but the fabrics in their study were coated with graphene on the whole surface, the thermal conductivity was estimated and a test setup with a different principle was used. Lu et al [30] reported similar values to our graphene-functionalized fabrics, for twill woven PES fabric with similar thickness and weight as in our study. Thermal resistance was measured by a sweating guarded hot plate.…”
Section: Ftt Measurementssupporting
confidence: 90%
“…Abbas et al [4] reported higher values of 0.078 W/m.K for cotton woven fabrics coated with graphene, but the fabrics in their study were coated with graphene on the whole surface, the thermal conductivity was estimated and a test setup with a different principle was used. Lu et al [30] reported similar values to our graphene-functionalized fabrics, for twill woven PES fabric with similar thickness and weight as in our study. Thermal resistance was measured by a sweating guarded hot plate.…”
Section: Ftt Measurementssupporting
confidence: 90%
“…7 Evaporative thermal dissipation is one of the important factors affecting an athlete’s performance under high temperatures. 8 The human body achieves thermal stability and a dry and comfortable state by balancing metabolic thermal production, thermal loss, and sweat evaporation. 9,10 Thermal and humid comfort is particularly significant for athletes.…”
mentioning
confidence: 99%